The Number of Integers Divisible by a^k Except a^(k+l) b - Tongron , Yanapat; Paikhlaew, Kanyaphak (Science & Technology Asia, 2022)
For positive integers , let be the set of all integers divisible by except between and . Under certain condition on these integers, we obtain the explicit formula for , where denotes the number of elements in a finite set . We also provide bounds on and show that these are the best bounds by examples.